THE RELATIONSHIP BETWEEN CHLOROPHYLL-α AND TOTAL PHOSPHORUS (TOTAL-P) IN PERUPUK LAKE, PERHENTIAN RAJA SUB-DISTRICT, KAMPAR, RIAU - Andika Ramadhani; Asmika H. Simarmata; Budijono Budijono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
The province of Riau has many freshwater bodies that play a very important role in the lives of those around them. This study aimed to determine the relationship between chlorophyll a and Total-P (Total Phosphorus) concentrations and to assess the trophic status of Perupuk Lake in Perhentian Raja Sub-District, Kampar Regency, Riau Province. The research was conducted from October to December 2024 at three stations: Station 1 (inlet, no settlement), Station 2 (lake main basin with fish cages), and Station 3 (outlet with settlement and agricultural activity). Sampling was performed 5 times at 1-week intervals at the surface and at 2 Secchi depths. Parameters measured included chlorophyll a, Total-P, temperature, transparency (Secchi depth), pH, dissolved oxygen (DO), free carbon dioxide (CO2), and nitrate. Results showed that chlorophyll a concentration ranged from 11.04 to 14.14 µg/L, with the highest at Station 2 (14.14 µg/L) and the lowest at Station 1 (11.04 µg/L). Total-P concentrations ranged from 0.0168–0.0338 mg/L, following the same pattern: highest at Station 3 (0.0338 mg/L) and lowest at Station 1 (0.0168 mg/L). Simple regression analysis showed a non-significant relationship between Total-P and chlorophyll-a (R² = 0.0266–0.0774), indicating that, in mesotrophic waters, other factors, such as light and nitrogen availability, also influence chlorophyll-a concentration. Based on chlorophyll a and Total-P concentrations, Perupuk Lake is categorized as a mesotrophic water body, with supporting parameters within optimal ranges for aquatic organisms.